Parenting a child with a traumatic brain injury: Experiences of parents and health professionals - Brown, F.; Whittingham, K.; Sofronoff, K.; Boyd, Roslyn (2013)
Objective: To qualitatively explore the experiences, challenges and needs of parents of children with traumatic brain injury (TBI) in order to inform future intervention research through incorporation of participant knowledge and experience. Methods: Parents of children with TBI (n=10) and experienced health professionals in paediatric rehabilitation (n=5) took part in focus groups or individual interviews. Audio recordings were transcribed verbatim and an inductive thematic analysis performed. Findings: Participants reported that, beyond the impact of the injury on the child, TBI affects the entire family. Parents need to adjust to and manage their child's difficulties and can also experience significant emotional distress, relationship discord and burden of care, further adding to the challenges of the parenting role. Parents can feel isolated and the importance of empowerment, support and information was emphasized. Coping styles of disengagement and avoidance were often reported, despite acknowledgement that these were not beneficial. Conclusions: Parenting interventions may provide essential support for parents in adjusting to and managing their child's difficulties and the efficacy of existing programmes needs evaluation. Addressing parent emotional adjustment and coping strategies is vital following paediatric TBI, given the impact on parent well-being and the potential negative effects on child outcomes through reduced parenting effectiveness. Group programmes may enable connection and support. © 2013 Informa UK Ltd.